Lingkungan Kerja dan Komitmen Organisasi serta Pengaruhnya terhadap Kepuasan Pegawai - Mardikaningsih, Rahayu; Sinambela, Ella Anastasya (Forum Kerjasama Pendidikan Tinggi, 2022)
Employees are one of the company's assets to survive in the midst of competition so that improving the quality of employees and creating a conducive work environment is also needed. Currently, companies need employees who are committed to the company, but it requires a work environment that supports it. In this study, conducting research on company employees in Surabaya, purposive sampling technique is the choice for sampling with the results of the number of respondents obtained as many as 55 respondents. Multiple linear regression analysis was used for this research, which when concluded from the research results obtained that the work environment and organizational commitment affect employee satisfaction. Companies need to increase organizational commitment and create a conducive environment to increase employee satisfaction